2015
DOI: 10.1517/13543784.2015.1099626
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapies and vaccines against the human respiratory syncytial virus

Abstract: Based on the results of various immunization strategies and therapeutic approaches, it is likely that the most effective strategy against hRSV will be a prophylactic tool aimed at developing a strong antiviral T-cell response capable of both, promoting the generation of hRSV-specific high affinity antibodies and leading the protective immunity required to prevent the disease caused by this virus. Alternatively, if prophylactic strategies fail, antiviral drugs and novel passive immunity strategies could signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 127 publications
0
20
0
Order By: Relevance
“…While a number of risk factors have been identified that are associated with the chance of severe RSV infection, the majority of RSV hospitalizations occur in previously healthy children (3). Currently, the only approved RSV-specific therapy is prophylactic treatment with palivizumab (4, 5). However, preventative treatment with palivizumab is restricted to high-risk infants and therefore there is currently no approved method to prevent severe RSV-induced disease in otherwise healthy children (6).…”
Section: Introductionmentioning
confidence: 99%
“…While a number of risk factors have been identified that are associated with the chance of severe RSV infection, the majority of RSV hospitalizations occur in previously healthy children (3). Currently, the only approved RSV-specific therapy is prophylactic treatment with palivizumab (4, 5). However, preventative treatment with palivizumab is restricted to high-risk infants and therefore there is currently no approved method to prevent severe RSV-induced disease in otherwise healthy children (6).…”
Section: Introductionmentioning
confidence: 99%
“…supportive care [33][34][35]. Therefore, novel therapeutics are needed to reduce the severity of RSV infection and limit hospital admissions.…”
Section: Resultsmentioning
confidence: 99%
“…One major representative of such ineffective efforts was the Formalin-Inactivated hRSV vaccine (FI-RSV), which actually led to enhanced disease in infants, causing a predisposition to an exacerbated immunopathology due to a strongly biased Th2-like immune response [ 23 , 24 , 25 ]. Currently, a few vaccine prototypes are being developed, with most of them aiming to diminish the Th2-like immune response observed in the hRSV infection [ 26 , 27 , 28 , 29 , 30 ]. Among those, our laboratory has generated a vaccine prototype consisting of a recombinant Mycobacterium bovis Bacillus Calmette–Guérin (BCG) that expresses the hRSV Nucleoprotein (rBCG-N), with promising results such as protective cellular and humoral responses [ 29 , 30 ].…”
Section: General Features Of Human Respiratory Syncytial Virus (Hrmentioning
confidence: 99%